2007
DOI: 10.1074/jbc.m608265200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Transcript Encoding the Proline-rich Membrane Anchor of Globular Muscle Acetylcholinesterase

Abstract: AChE in cultured myotubes were markedly reduced. In addition, calcitonin gene-related peptide, a known motor neuron-derived factor, and muscular activity were able to suppress PRiMA expression in muscle; the suppression was mediated by the phosphorylation of a cAMP-responsive element-binding protein. In accordance with the in vitro results, sciatic nerve denervation transiently increased the expression of PRiMA mRNA and decreased the phosphorylation of cAMP-responsive element-binding protein as well as its act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…The strong expression of PRiMA protein and G 4 AChE in fast-twitch muscles is consistent with previous results on PRiMA mRNA expression, i.e. the tibialis contains an approximately 10-fold higher level of PRiMA mRNA than the soleus [9]. The developmental change of PRiMA-linked G 4 AChE in muscle correlates with an increase in muscular activity and muscle loading [15][16][17], which leads to the differentiation of fast-twitch and slow-twitch muscle fibers.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The strong expression of PRiMA protein and G 4 AChE in fast-twitch muscles is consistent with previous results on PRiMA mRNA expression, i.e. the tibialis contains an approximately 10-fold higher level of PRiMA mRNA than the soleus [9]. The developmental change of PRiMA-linked G 4 AChE in muscle correlates with an increase in muscular activity and muscle loading [15][16][17], which leads to the differentiation of fast-twitch and slow-twitch muscle fibers.…”
Section: Discussionsupporting
confidence: 91%
“…The major form is the asymmetric collagen-tailed AChE, which is attached to the synaptic basal lamina [18]. Our study and others have shown that G 4 AChE is linked by PRiMA and localized in the membranes of postsynaptic and presynaptic cells [9]. At NMJs, three cell types can contribute to synaptic AChE: the postsynaptic muscle cell, the presynaptic Sections from adult rat tibialis after 7 days of denervation (right) and sham-operated (left) were triple stained with Alexa 647-conjugated a-bungarotoxin (pseudo-blue) for postsynaptic AChR, anti-synaptotagmin (SV48; red) for presynaptic nerve terminal, and anti-PRiMA (green), and examined by confocal microscopy.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Hence, neuronal AChE was the first synaptic protein analyzed thus in this study. Different forms of AChE (based on the same catalytic subunit and ACHE gene) have been identified at various locations (e.g., globular and collagen-tailed forms) (Xie et al, 2007), and these were distinguished here.…”
Section: Resultsmentioning
confidence: 98%